Predicting psychological abuse in intimate relationships: Insights from perceptions, victimisation, and perpetration histories in South Africa - Fakunmoju, Sunday; Rasool, Shahana (Social Work/Maatskaplike Werk, 2025)
This study examines the factors contributing to the likelihood of psychological abuse in intimate relationships in South Africa. Using data from 454 adults aged 20–51, the study explores how perceptions, past victimisation and previous perpetration shape the propensity to engage in psychological abuse: verbal aggression, isolation/control, neglect/ignoring, and economic/financial abuse. Participants were recruited through social media platforms, and data collection utilised a validated scale developed for the South African context. The findings identified isolating, controlling, ignoring and neglecting behaviours as the most common forms of psychological abuse. Past victimisation and perpetration of psychological abuse strongly predict future abuse, with past abusive behaviours significantly influencing the likelihood of future tendencies. Younger participants were more likely to engage in economic abuse, highlighting an age-related pattern. Additionally, while perceptions of abuse influenced behaviours differently across relationship statuses, the link between past experiences and future abuse remained consistent. These results emphasise the need for social workers to focus on preventing abuse, implementing trauma-informed interventions to support victims and rehabilitate perpetrators, enhancing recovery efforts, and developing educational programmes and policy interventions to break the cycle of violence. Future research should consider longitudinal designs to better understand the dynamics of abuse over time in South Africa.